Frequency of hypothyroidism in patients with benign breast diseases. - Iftikhar, Javeria; Danish Abdus Samad; Zehra , Fatima; Zehra, Batool; Zubair, Rabbia; Mohd Ali Channa (International Journal of Endorsing Health Science Research, 2024)
Background: Non-malignant breast pathologies are a common reason for female patients to seek medical attention in surgical outpatient departments globally. Hormonal factors, particularly hypothyroidism, have been frequently implicated in these pathologies. This study aimed to assess the frequency of hypothyroidism in patients with benign mammary disorders. Methodology: A prospective observational study was conducted at Hamdard University Hospital's Surgical OPD from October 2022 to September 2023. Data were collected from female patients presenting with symptoms of benign breast diseases, excluding those with a history of hypothyroidism. Screening for hypothyroidism was performed through serum thyroid stimulating hormone (TSH) assessment. Clinical data, TSH levels, and patient demographics were recorded. The relationship between benign breast disease (BBD) symptoms and hypothyroidism was analyzed. Results: The average age of the subjects was 32 ± 10 years. Mastalgia was the most commonly reported complaint among patients with BBD (56.2%, n=109), followed by breast lump (23.2%, n=45) and nipple discharge (20.6%, n=40). The overall frequency of hypothyroidism was 30.4% (n=59). Hypothyroidism was more prevalent in patients with nipple discharge (35%, n=14) compared to mastalgia (32.1%, n=35) and breast lump (22.2%, n=10) (p=0.373). It was also more common in the 18-25 age group (39%, p=0.122). Eighty-two percent of patients did not exhibit symptoms of hypothyroidism. Among symptomatic patients, 18% experienced both weight gain and constipation, with a mean serum TSH level of 5.6 ± 3.9 mIU/L in this subgroup (p=<0.001). Hypothyroid patients had higher average TSH levels in the mastalgia group (7.5 mIU/L) compared to the breast lump (6.6 mIU/L) and nipple discharge (5.5 mIU/L) groups (p≤0.001). Conclusion: Screening for serum TSH levels should be considered in patients presenting with symptoms of BBD due to the high frequency of hypothyroidism in this population. Assessing thyroid function may aid in the management of women with benign breast symptoms.